Pengaruh Tunneling Incentive, Mekanisme Bonus Dan Exchange Rate Terhadap Keputusan Perusahaan Melakukan Transfer Pricing - Patriot Jaya Ayshinta; Henri Agustin; Mayar Afriyenti (Jurnal Eksplorasi Akuntansi, 2019)
This research aims to examine to analyze the effect of tunneling incentive, bonus scheme and exchange rate on the company’s decision to do transfer pricing. The population in this research are manufacturing companies listed in Indonesia Stock Exchange (IDX) in 2014 until 2017. The sample of study was determined by using purposive sampling method, and that total sample 48 manufacturing companies. The data used is secondary data. The technique of collecting data by documentation at www.idx.com. The analytical method used is Panel Regression Analysis with SPSS22 software. /This research use logistic regression analysis as analysis /method.The result of analysis in this research showed that tunneling incentive and bonus scheme had no effect on ithe company’s decision to do transfer pricing. Exchange rate had a significant effect on the company’s decision to do transferi pricing